Androgenny i glukokortykoidowy status predyktorem sukcesu zawodników w podnoszeniu ciezarów - Obminski, Z.; Opaszowski, B. H.; Szewczyk, R.; Choros, M. (Medycyna sportowa, 2001)
Resting cortisol and testosterone levels were determined in 6 weight lifters throughout 4 training microcycles lasting 17 days in total. The athletes were preparing for Olympic Games Sydney 2000. No significant between-subject differences were found for cortisol while testosterone differed markedly between subjects. Those, in whom testosterone fluctuations were small, achieved better competition results than the other ones. Thus, stability of resting testosterone concentrations throughout a long-lasting training period may be regarded as a predictor of success in weight lifting.